Childhood interstitial lung disease: A systematic review. Issue 12 (30th April 2015) - Hime, Neil J; Zurynski, Yvonne; Fitzgerald, Dominic; Selvadurai, Hiran; Phu, Amy; Deverell, Marie; Elliott, Elizabeth J; Jaffe, Adam
Summary: Objectives: Childhood interstitial lung disease (chILD) is a group of rare chronic and complex disorders of variable pathology. There has been no systematic review of published chILD research. This study aimed to describe chILD classification systems, epidemiology, morbidity, treatments, outcomes, and the impact of chILD on families and the burden on health services. Methods: A systematic literature search for original studies on chILD was undertaken in the major biomedical databases to the end of December 2013. Epidemiological studies, case series and studies describing classification systems were included. Single case studies were excluded. Results: The search yielded 37 publications that met study criteria. Four different chILD classification systems have been proposed in the past decade. The incidence of chILD has been estimated at 0.13–16.2 cases/100, 000 children/year. One to five new cases presented to individual hospitals each year. In developed countries, the median mortality was 13% (6–19%). Morbidity and outcomes were highly variable and not systematically reported. Corticosteroids and hydroxychloroquine were the most common treatments. The impact of chILD on families and the burden on health services has not been studied. Conclusions: The heterogeneity of the chILD group of disorders, different determinations of what constitutes a chILD disorder and, a paucity of large epidemiological studies precludes consolidation of results across studies. Consensus on chILD classification is needed to support diagnosis and allow direct comparisons of research evidence. Active disease surveillance and international patient registries are required to advance understanding and management of chILD.Pediatr Pulmonol. 2015; 50:1383–1392. © 2015 Wiley Periodicals, Inc.